SOSIALISASI PENTINGNYA LOKASI UMKM PADA GOOGLE MAPS SEBAGAI BENTUK DIGITAL MARKETING - Yusuf, Muhammad; Rahman, Zia Urr; Helfenta, Helfenta (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2024)
MSMEs are one of the economic activities that support the economic growth of the community in Nagari Tanah Bakali Inderapura. The limited knowledge of MSME owner about the use of technology in running a business that causes the business to be run is still limited in scope. This activity was carried out to inform MSME owners about Google Maps and its benefits, as well as provide assistance in business registration on the feature. This community service activity is carried out in two stages, namely preparation and implementation. Preparations were made to find out the problems faced by MSME owners and prepare pamphlets about the stages of registering on Google Maps. At the implementation stage, socialization was carried out about Google Maps and its uses, as well as accompanying business registration on the feature. The results of the activity show that activities can change the views of MSME owners in utilizing technology, especially Google Maps.